Inside Back Cover: Site‐Specific Dynamics of β‐Sheet Peptides with DPro–Gly Turns Probed by Laser‐Excited Temperature‐Jump Infrared Spectroscopy (ChemPhysChem 9/2016). Issue 9 (20th April 2016) - Popp, Alexander; Scheerer, David; Chi, Heng; Keiderling, Timothy A.; Hauser, Karin
Abstract : The Inside Back Cover picture shows how relaxation kinetics of β‐sheet peptides are monitored with infrared spectroscopy after a rapid temperature‐jump. More information can be found in the Full Paper by K. Hauser and co‐workers onpage 1273 in Issue 9, 2016 (DOI:10.1002/cphc.201501089 ).